Quantitative Analysis of Retinal Vasculature in Rhegmatogenous Retinal Detachment Based on Ultra-Widefield Fundus Imaging - Feng, Bingkai; Su, Wenxin; Chen, Qingshan; Gan, Run; Wang, Mingxuan; Wang, Jiantao; Zhang, Jiayi; Yan, Xiaohe (Frontiers in Medicine, 2022)
Purpose To quantitatively analyze retinal vascular morphological features including vascular density, caliber, and tortuosity in rhegmatogenous retinal detachment (RRD). Methods A total of 244 patients with RRD and 400 healthy controls (HC) were included. Retinal fundus images were collected using OPTOS PLC Daytona P200T. Retinal images were divided into RRD and non-RRD region of interests (ROIs). All visible retinal fundus vessels were then extracted mainly based on edge detection within ROI to form whole-vascular image. Retinal vasculature parameters including vascular density, caliber, and tortuosity were calculated. Results For the absolute density, the mean rank value of normal controls was significantly higher than that in non-RRD (p < .001). A consistent tendency of significant vascular density increasement from non-RRD to RRD (p < .001). The average and median diameter of normal controls were both significantly larger than RRD (p <.001). The average and median diameters was also appeared significantly thinner in non-RRD. Unweighted and width-inversely-weighted vascular tortuosity in RRD and non-RRD comparison exhibited non-significant difference. All types of tortuosity calculated from HC were significantly larger (p <.001) in values compared to RRD. All types of tortuosity values of HC significantly higher than non-RRD. Compare with non-RRD, RRD was significantly larger in area-weighted, length-weighted, and width-weighted vascular tortuosity. Conclusions This study showed that RRD affects both the quantity and morphology of retinal vasculature including RRD and non-RRD areas. Smaller average and medium vascular diameter and tortuosity value were found in RRD. However, the absolute vascular density, the average and median diameter and tortuosity value were also reduced in non-RRD although the retina is still attached. This work indicates that RRD may affect the retinal vasculature beyond the detached retina.